Genus-Wide Pan-Genome Analysis of Oryza Calcium-Dependent Protein Kinase Genes and Their Related Kinases Highlights the Complexity of Protein Domain Architectures and Expression Dynamics - Fu Shi; Li Li; Mingjie Chen; Junli Chang; Min Tu; Guangyuan He; Yin Li; Guangxiao Yang (Plants)
The Oryza genus serves not only as a gene pool for rice improvement but also as a model system for plant evolutionary research. Calcium-dependent protein kinases (CPKs) function as both effectors and sensors in calcium signaling and play versatile roles in plant development and stress responses. Four kinase families, namely CPK-related kinases (CRKs), phosphoenolpyruvate carboxylase kinases (PPCKs), PPCK-related kinases (PEPRKs), and calcium- and calmodulin-dependent kinases (CCaMKs), are frequently called CPK-related kinases. This study utilized evolutionary genomics approaches and provided the pan-genome repertoires of CPKs and their related kinases in 34 Oryza genomes by leveraging the rich genomics resources of the Orzya genus. Gene duplication analysis revealed that distinct duplication types contributed to expanding CPKs and their related kinases in wild rice. We depicted the protein domain architectures of CPKs and their related kinases, highlighting the complexity of EF-hand motifs in CPKs and CCaMKs. Transcriptome analysis determined that alternative splicing was a mechanism contributing to the diversity in the domain architectures of CPKs and CCaMKs. We also generated the expression atlas of CPKs and their related kinases in multiple species of Oryza genus, emphasizing divergent homoeolog expression patterns across tissues and species in allotetraploid wild rice. Collectively, our Oryza-wide analysis of CPKs and their related kinases revealed their evolutionary trajectories and highlighted their diversified domain architectures and expression dynamics, providing gene resources of wild relatives for rice improvement.